Effective Learning Strategies to Improve Learning Outcomes - Euis Latipah; Harlyan Nurpatimah; Nisrina Syahla; Siti Jenab Setiawati (Penerbit Hellow Pustaka, 2025)
Learning strategies are plans and methods used by educators to facilitate students' learning processes and effectively achieve learning objectives. This article discusses various learning strategies that can be implemented in the classroom, such as cooperative learning, problem-based learning, and contextual learning. Cooperative learning emphasizes collaboration among students in small groups to build shared understanding. Problem-based learning encourages students to actively seek solutions to real-life problems, thereby enhancing critical and creative thinking skills. Meanwhile, contextual learning connects subject matter with everyday life situations to facilitate students' understanding and application. Furthermore, this article highlights the importance of selecting strategies that are appropriate to student characteristics, learning objectives, and available resources. With appropriate learning strategies, it is hoped that student motivation, participation, and learning outcomes can be significantly improved. Research and practice show that learning success is greatly influenced by teachers' ability to manage and implement varied and adaptive learning strategies. Therefore, the development of teacher competency in learning strategies needs to be continuously encouraged to create an effective and enjoyable learning process for students.